Changes in Ocular Blood Flow after Ranibizumab Intravitreal Injection for Diabetic Macular Edema Measured Using Laser Speckle Flowgraphy. (10th February 2020) - Toto, Lisa; Evangelista, Federica; Viggiano, Pasquale; Erroi, Emanuele; D'Onofrio, Giada; Libertini, Daniele; Porreca, Annamaria; D'Aloisio, Rossella; Mariacristina, Parravano; Di Antonio, Luca; Di Nicola, Marta; Mastropasqua, Rodolfo
Abstract : Purpose . To evaluate the effects of intravitreal ranibizumab (IVR) treatment on the blood flow of the optic nerve head (ONH) and of retinal vessels of the peripapillary region of eyes with diabetic macular edema (DME) assessed using laser speckle flowgraphy (LSFG). Methods . Forty eyes of 30 patients treated with IVR for DME were included in this prospective clinical study. Mean blur rate (MBR) and relative flow volume (RFV) of the ONH and of a superior retinal artery and an inferior retinal vein of the peripapillary region were measured using LSFG at baseline, 2 weeks (T1), and 1 month (T2) after IVR injection. In addition, best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were measured in all cases. Results . The BCVA improved and CRT decreased significantly during the follow-up period (p < 0.010 ). MBR-related parameters of the ONH such as MBR of all area (MA), MBR of vascular area (MV), and MBR of tissue area (MT) decreased significantly at 2 weeks after IVR compared to baseline values (MA, p = 0.046 ; MT, p = 0.023 ; MV, p = 0.025 ), with no significant change at T2 compared to T1. MBR of the retinal artery and vein changed significantly at 2 weeks after IVR and did not change significantly thereafter (p = 0.004 and p = 0.01, respectively). The median of RFV of the 2 vessels was 269.5 (221.6–285.5) and 306.8 (285.6–372.4) at baseline and 199.7 (152.4–204.7) and 259.1 (140.9–336.8) at 4 weeks, respectively (p = 0.292 and p = 0.002, respectively). Blowout time changed significantly in ONH from 47.6 (44.2–50.2) at baseline to 54.4 (46.8–65.3) at 1 month after IVR (p = 0.001 ). Conclusion . IVR injection leads to a reduction of ocular blood flow both in the ONH and in the retinal peripapillary vessels associated with peripapillary vessel constriction. The reduction of CRT and related improvement of vision may be related to the changes in ocular blood flow.